E-030 Radiopacity optimization of a novel liquid embolic. (22nd July 2018) - Merritt, W; Byakeddy, T; Caime, W; Huckleberry, A; Becker, T; Ducruet, A
Abstract : Introduction: While there have been notable advances in minimally invasive methods for the embolization of intracranial aneurysms, there remains a paucity of high-performing liquid embolic materials suitable for aneurysm occlusion. The purpose of this project is to develop a liquid embolic (PPODA-QT) for the endovascular treatment of aneurysms to significantly increase therapeutic effectiveness while minimizing surgical risks. This study assesses and optimizes the visibility of PPODA-QT during injection. Materials and methods: PPODA-QT liquid and solid samples were gelled within both aneurysmal and mechanical testing molds to create samples for radiopacity and mechanical testing. For radiopacity testing, PPODA-QT was assessed with a fluoroscope (BV-Pulsera, Philips) using a visualization test standard (ASTM F640–79) to quantify the optical density of the resulting material. Optical density data was determined for PPODA-QT formulations using various concentrations of liquid and solid contrast agents and these were compared against metal coils and Onyx. The results were verified to validate acceptable values. Next, for mechanical testing, samples were characterized with a hybrid-rheometer (HR2 Hybrid Rheometer, TA Instruments). The mechanical testing simulated acceptable ranges of flow pressures, compressive stresses, shear, and wear rates exhibited by blood flow to side-wall and bifurcation aneurysms. Results and discussion: Elastic modulus, shear modulus, and gelation time were evaluated for the varying formulations of PPODA-QT to identify whether differences in contrast agent and/or contrast concentration compromised the resulting material's integrity. A graph of viscosity and phase angle shows the polymerization of the PPODA-QT within an acceptable procedural timeframe (figure 1A). Radiopacity was quantified in three visualization scenarios, following the ASTM F640–79 protocol. These real-time visualization steps simulated injection into an appropriate vascular model (aneurysm approximation – figure 1B). The time-lapse visualization allowed quantification of percent-loss of contrast over time, as the PPODA-QT was submerged in Ringer's solution. The fluoroscope images were analyzed using Adobe Photoshop software. Conclusions: The PPODA-QT device introduces innovations in delivery control, aneurysm healing effects, and reduced downstream emboli that have not been consistently addressed by previous treatment options. This venture represents a collaboration between bioengineering and neurosurgery fields, namely, the Northern Arizona University's Bioengineering Devices Lab and Barrow Neurological Institute. This study will ultimately prove important in providing physicians with a new and effective weapon in their arsenal for the treatment of cerebral aneurysms. Disclosures: W. Merritt: 1; C; National Institute of Health. 5; C; Northern Arizona University, Aneuvas Technologies Inc. T. Byakeddy: 1; C; National Institute of Health. W. Caime: 1; C; National Institute of Health. A. Huckleberry: 1; C; National Institute of Health. T. Becker: 1; C; National Institute of Health. 4; C; Aneuvas Technologies Inc. A. Ducruet: 5; C; Barrow Neurological Institute.